Towards Predicting Progression to Severe Dengue. Issue 6 (June 2020) - Robinson, Makeda; Einav, Shirit
Abstract : There is an urgent need for prognostic assays to predict progression to severe dengue infection, which is a major global threat. While the majority of symptomatic dengue patients experience an acute febrile illness, 5–20% progress to severe infection associated with significant morbidity and mortality. Early monitoring and administration of supportive care reduce mortality and clinically usable biomarkers to predict severe dengue are needed. Here, we review recent discoveries of gene sets, anti-dengue antibody properties, and inflammatory markers with potential utility as predictors of disease progression. Upon larger scale validation and development of affordable sample-to-answer technologies, some of these biomarkers may be utilized to develop the first prognostic assay for improving patient care and allocating healthcare resources more effectively in dengue endemic countries. Highlights: Until recently there have been no clinically usable biomarkers to accurately predict which patients will progress to severe dengue, a major global threat. A 20-gene set that is strongly associated with the progression to severe dengue and represents a predictive signature that is generalizable across ages, host genetic factors, virus strains, and sample types was recently discovered using a multicohort analysis framework that integrates biologically heterogeneous data sets. Recently discovered anti-dengue antibody properties, inflammatory, apoptotic and metabolic markers, some of which are generalizable across cohorts, also have potential utility as predictors of dengue disease progression. Some of these biomarkers may be utilized to develop the first prognostic assay for improving patient care and allocating healthcare resources more effectively in dengue endemic countries.